2010
DOI: 10.1016/j.crci.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Étude structurale de britholite au césium Sr7La2Cs(PO4)5(SiO4)F2

Abstract: e ´tudes ont montre ´que les britholites sont capables de recevoir des radionucle ´ides comme le ce ´sium ou les actinides. Dans ce cadre, trois compositions de formules respectives Sr 8 LaCs(PO 4 ) 6 F 2 , Sr 7 La 2 Cs(PO 4 ) 5 (SiO 4 )F 2 et Sr 2 La 7 Cs(SiO 4 ) 6 F 2 ont e ´te ṕre ´pare ´es par re ´action a `l'e ´tat solide. Mais il semble qu'uniquement la composition monosilicate ´e a e ´te ´obtenue a `l'e ´tat pur. Dans ce pre ´sent travail, la diffraction des rayons X et la re ´sonance magne ´tique nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In order to get a better understanding of the evolution of their properties with the substitution degree, a systematic study of lanthanide-substituted fluoro-and oxyapatites has been undertaken in our laboratory [36][37][38][39][40][41]. In this paper, we investigate the ionic conductivity of the Ca 6 La 4 (PO 4 ) 2 (SiO 4 ) 4 F 2 and Ca 4 La 6 (SiO 4 ) 6 F 2 samples using impedance spectroscopy.…”
Section: R E ´S U M E Dansmentioning
confidence: 99%
“…In order to get a better understanding of the evolution of their properties with the substitution degree, a systematic study of lanthanide-substituted fluoro-and oxyapatites has been undertaken in our laboratory [36][37][38][39][40][41]. In this paper, we investigate the ionic conductivity of the Ca 6 La 4 (PO 4 ) 2 (SiO 4 ) 4 F 2 and Ca 4 La 6 (SiO 4 ) 6 F 2 samples using impedance spectroscopy.…”
Section: R E ´S U M E Dansmentioning
confidence: 99%
“…Reports have shown that caesium and strontium can be incorporated into cement type and zeolite cement blend materials [26,27], in aluminosilicates with the use of porous glass-ceramic matrices [28], in tungstate-based glass-ceramics [29], into NZP lattice by hydrothermal method [30] and immobilization of caesium into britholite (Sr 7 La 2 Cs(PO 4 ) 5 (SiO 4 )F 2 ) [31]. Bogdamov and Kuznetsov reported alumino silicophosphate ceramics as matrices for the immobilization of 90 Sr and 137 Cs [32].…”
Section: Introductionmentioning
confidence: 99%